1974
DOI: 10.1084/jem.139.5.1204
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Control of the Immune Response to Staphylococcal Nuclease

Abstract: A number of inbred and congenic resistant strains of mice were immunized with staphylococcal nuclease (Nase). Antibody responses were measured in the sera of the animals by a sensitive method involving inhibition of enzymatic hydrolysis of DNA, High responder strains included A/J, DBA/2, BALB/c, AKR/J, C57BR, and SJL/J. DBA/1 and C57BL/6 mice were low responders. The strain distribution of anti-Nase response potential was compatible with the relevant immune response gene(s) being linked to the murine major his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

1974
1974
1982
1982

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 68 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…The finding that the antibodies from responder and nonresponder mice can share idiotypic determinants is in agreement with the recently published observations of Fathman et al [34], who investigated the genetic expression ofidiotypic determinants on antibodies directed against staphylococcal nuclease, an antigen to which the response is also under Ir gene control [55].…”
Section: Idiotype Studies Using Anti-gl4) Antibodiessupporting
confidence: 81%
“…The finding that the antibodies from responder and nonresponder mice can share idiotypic determinants is in agreement with the recently published observations of Fathman et al [34], who investigated the genetic expression ofidiotypic determinants on antibodies directed against staphylococcal nuclease, an antigen to which the response is also under Ir gene control [55].…”
Section: Idiotype Studies Using Anti-gl4) Antibodiessupporting
confidence: 81%
“…Further investigations showed that the levels of antibody produced to nuclease in mice were under genetic control by genes in the/1" region of the H-2 complex, and thus defined another Ir gene, termed Ir-Nase [16]. Further investigations showed that the levels of antibody produced to nuclease in mice were under genetic control by genes in the/1" region of the H-2 complex, and thus defined another Ir gene, termed Ir-Nase [16].…”
mentioning
confidence: 99%
“…Other Antisera and Antigen-Antibody Complexes.--Purified staphylococcal nuclease (nuclease) and mouse antibody to nuclease purified by affinity chromatography were prepared using methods previously described (20,21). Goat antimouse Ig was prepared by immunizing a single goat with 1 mg of immunoelectrophoretically pure mouse Ig in complete Freund's adjuvant subcutaneously three times (2 wk apart).…”
mentioning
confidence: 99%